Mengatasi Perilaku Bullying Siswa Melalui Konseling Kelompok Teknik Role Playing - Muhammad Asro; DYP Sugiharto; Awalya Awalya (Indonesian Journal of Educational Counseling, 2021)
OVERCOMING STUDENT BULLYING BEHAVIOUR THROUGH ROLE-PLAYING TECHNIQUE GROUP COUNSELING. This study aims to determine the impact of group counselling on role-playing techniques on student bullying behaviour at SMP Negeri 1 Terisi Indramayu. The pretest-posttest non-equivalent control group experimental design was used in this study by involving a total of 14 students of class VIII who were selected using the purposive sampling technique as participants and divided into two groups. Bullying behaviour data were collected through a form of bullying scale-perpetration. The data analysis technique used is nonparametric statistics using the Wilcoxon test with a significant level of 5%. The results showed that there was a significant decrease in bullying behaviour in the experimental group (M=18.71) compared to the control group (M=33.43).